Determining optimum roasting conditions of hematite magnetization with temperature-coke mixture copula - (:unkn) unknown (My University, 2022)
In this study, the magnetization behavior of Türkiye’s volcanic kafa ore (VKO) was investigated with reduction roasting. The Kafa ore contains mainly hematite which is the main source of iron along with a small amount of goethite and gangue minerals namely quartz and calcite. Since it is necessary to separate the gangue from iron-bearing ore and low magnetic susceptibility of hematite; the magnetization of hematite was carried out by reduction roasting. By doing so, it was aimed to separate the magnetized iron ore from the gangue by magnetic separation. In order to achieve this purpose, an experimental design was planned which has 5 different sets of temperature and 3 different sets of coke mixture ratios. The temperature ranges from 400⁰C to 900⁰C by 100⁰C increment in every set. Similarly, the coke that was used as a reducing agent mixture, takes values of 30, 40, and 50%. Following the experimental setup, roasted VKOs were subjected to low-intensity dry magnetic separation at 750 oersteds magnetic field strength. The effects of temperature and amount of coke on the transformation of hematite to magnetite and the determination of mineralization of the concentrate obtained after magnetic separation were investigated by X-ray diffraction. Fe grade and recovery were determined by using chemical analysis, and then the optimization of the experiments was determined with Fe% recovery that was obtained after magnetic separation. X-ray diffraction patterns show that magnetite transformation begins at 600 ⁰C after reduction roasting. After magnetic separation, the effect of the temperature and the effect of the coke mixture on Fe% recovery were investigated. The relationship between Fe% recovery and temperature was shown as a linear correlation. The recovery rate can be expressed as y = 0.2114x - 77,711 where y is the recovery rate and x is the temperature. The fitness of the model is very high with an R² = 0.886. However, the effect of the coke mixture on Fe% recovery could not be detected. The fitness of the model confirms this indifference by R² = 0.0078. When the coke mixture was kept constant, iron recovery efficiencies were lower than 57% till 600°C and it sharply increased by temperature and peaked at 800°C. A peculiar condition was detected at 700°C and a 50% coke mixture with a 90% Fe-recovery rate. Another highefficiency point was observed at 800⁰C and a 30% coke mixture with an 89% Fe-recovery. In conclusion, two optimal conditions were found with different trade-offs The first one requires a lower temperature while needs more coke. The second condition needs more temperature while the coke requirement is lower than the first one. These conditions can be traded regarding the following conditions: availability of energy, cost of marginal temperature increment, availability of coke, and cost of coke.
Keywords: Metalurji ve Malzeme Mühendisliği; Üretim Metalurjisi; Demir Dışı Metal Üretimi; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Production Metallurgy; Non-Ferrous Alloy Production; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING